2015
DOI: 10.1101/029603
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Adjudicating between face-coding models with individual-face fMRI responses

Abstract: The perceptual representation of individual faces is often explained with reference to a norm-based face space. In such spaces, individuals are encoded as vectors where identity is primarily conveyed by direction and distinctiveness by eccentricity. Here we measured human fMRI responses and psychophysical similarity judgments of individual face exemplars, which were generated as realistic 3D animations using a computer-graphics model. We developed and evaluated multiple neurobiologically plausible computationa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 46 publications
2
15
1
Order By: Relevance
“…In contrast, the representational geometries of faces in the right OFA were most associated with lowlevel image-based properties, such as pixel similarity and features extracted with Gabor filters that simulate functioning of early visual cortex. While previous studies had shown that low-level properties of images extracted with Gabor filters were associated with representational distances of faces in right FFA (Carlin & Kriegeskorte, 2017;Weibert et al, 2018), our results suggest that representations in right FFA use more complex combinations of stimulus-based features and relate to higher-level perceived and social properties. These results inform existing neurocognitive models of face processing (Haxby et al, 2000;Duchaine & Yovel, 2015) by shedding light on the muchdebated computations of face-responsive regions, and providing new evidence to support a hierarchical organisation of these regions from the processing of low-level image-computable properties in the OFA to higher-level visual features and social information in the FFA.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…In contrast, the representational geometries of faces in the right OFA were most associated with lowlevel image-based properties, such as pixel similarity and features extracted with Gabor filters that simulate functioning of early visual cortex. While previous studies had shown that low-level properties of images extracted with Gabor filters were associated with representational distances of faces in right FFA (Carlin & Kriegeskorte, 2017;Weibert et al, 2018), our results suggest that representations in right FFA use more complex combinations of stimulus-based features and relate to higher-level perceived and social properties. These results inform existing neurocognitive models of face processing (Haxby et al, 2000;Duchaine & Yovel, 2015) by shedding light on the muchdebated computations of face-responsive regions, and providing new evidence to support a hierarchical organisation of these regions from the processing of low-level image-computable properties in the OFA to higher-level visual features and social information in the FFA.…”
Section: Discussioncontrasting
confidence: 80%
“…These results thus suggest that the OFA and FFA both represent complex configurations of image-based information and not face identity per se. Some studies have also shown that even lower-level stimulus-based properties of face images, such as those computed by Gabor filters, explain significant variance in the representational geometries in the FFA (Carlin & Kriegeskorte, 2017) as well as OFA and pSTS (Weibert et al, 2018). On the other hand, other studies have shown that more high-level information, such as biographical information and social context, affects the similarity of response patterns to different faces in the FFA (Verosky et al, 2013;Collins et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Fourth, we assumed a bellshaped tuning function, which as far as we know is the only type of function used in research applying inverted encoding modeling [e.g., 9,38,31,15,13,11,12,10]. For other stimulus dimensions, such as those characterized by monotonically increasing or decreasing tuning functions (e.g., face dimensions; [44,5,45,43]), new simulations would be required. Finally, we assumed a homogeneous encoding population for the baseline condition.…”
Section: Discussionmentioning
confidence: 99%
“…For orientation stimuli, we chose to model channels as symmetrical Gaussians with Poisson noise based on previous literature, but there are other ways to characterize tuning functions that may be more appropriate for other types of stimuli. For example, face dimensions are often modeled using asymmetric sigmoidal tuning functions [44,5,45,43]. Also, another common assumption for neural channel noise is that it follows a Gaussian distribution [e.g., 6, 7], a common assumption implicit in inverted encoding modeling analyses of neuroimaging data [see 8,14].…”
Section: What About Other Encoding and Decoding Models?mentioning
confidence: 99%
“…To ensure that our decoding results did not depend on the choice of classifier, we repeated the MVPA using a representational similarity analysis (RSA) approach, with linear discriminant contrast (LDC) as a measure of dissimilarity between rule patterns (Carlin & Kriegeskorte, 2017;Nili et al, 2014). Cross-validated Mahalanobis distances were calculated for all 15 pairwise rule combinations and averaged to get within-and between-category rule pairs, for each ROI and participant, using all the voxels in the ROI and subject-specific ROIs defined using the different localizer tasks.…”
Section: Multivoxel Pattern Analysis (Mvpa) Of the Criterion Taskmentioning
confidence: 99%